Genre-Based Writing Instruction In Online Learning Environment: A Case Study In Indonesian Higher Education - Slamet Utomo; Titis Sulistyowati; Sri Surachmi W; Siti Marmoah; Lucky Restyanti Wahyu Utami (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2026)
This research investigated the effectiveness of asynchronous genre-based instruction (GBI) in improving the narrative writing proficiency of English as a Foreign Language (EFL) students in Indonesian higher education in post-pandemic. Using a single-group pre- and post-test quasi-experimental design, 16 students completed a seven-week writing intervention based on local folktales. Writing proficiency was assessed before and after the treatment. Statistical analysis using the Wilcoxon Signed-Rank Test revealed a significant improvement in students’ writing performance (p=0.006). notable progress was observed in the use of generic structures. However, students showed a decline in the use of time conjunctions and direct speech. These findings suggest that while asynchronous GBI enhances structural competence, additional scaffolding may be needed to strengthen linguistic feature deployment and narrative liveliness. The researchers also reported that the students had made some improvements on the generic structures. They made clear steps in organizing the flow of the story, started from introducing the story by setting a clear orientation. However, the frequency of time conjunction production decrease as well as the use of direct speech. They tend to only modify the background story and neglect few of the language features which actually very important to make the narrative more lively and enjoyable to read.